The Application of Criminal Law in Addressing Corruption Crimes: Strategies and Challenges - Mufty, Abdul Malik; Suhendar; Hasnia, Hasnia; Insani, Nursolihi; Rusyani, Herlin (Jurnal Smart Hukum (JSH), 2024)
Corruption poses a substantial challenge for Indonesia, affecting community life, national development, and state functioning. It leads to significant financial losses and economic repercussions for both perpetrators and the nation. To combat this issue, it's essential to harmonize legislation, enhance international cooperation, and develop an integrated approach to law enforcement while encouraging active community participation. Addressing corruption requires improvements in education, training, and the instillation of moral values. This research aims to understand the characteristics of normative legal knowledge and to explore legal regulations and their principles using a normative juridical approach, relying on secondary data analysis. Active prevention of corruption and a proactive role for corruption courts are crucial. Key findings suggest the need for rigorous law enforcement, the abolition of gratuities, increased transparency, and enhanced public ethics. Collaboration among the government, law enforcement, and the community is vital to effectively tackle corruption. Fair law enforcement and legal certainty must be ensured to build a collective conviction among stakeholders. A multifaceted approach is necessary for effective corruption eradication, including system improvements, educational campaigns, and repressive actions. Sustained efforts can minimize corruption's negative impacts, foster public trust, attract investors, and uphold national dignity while deterring corrupt activities. Furthermore, maximizing the recovery of state funds lost to corruption is essential for the nation’s integrity and development.